Demonstration of chemistry at a point through restructuring and catalytic activation at anchored nanoparticles. Issue 1 (December 2017) - Neagu, Dragos; Papaioannou, Evangelos; Ramli, Wan; Miller, David; Murdoch, Billy; Ménard, Hervé; Umar, Ahmed; Barlow, Anders; Cumpson, Peter; Irvine, John; Metcalfe, Ian
Abstract Metal nanoparticles prepared by exsolution at the surface of perovskite oxides have been recently shown to enable new dimensions in catalysis and energy conversion and storage technologies owing to their socketed, well-anchored structure. Here we show that contrary to general belief, exsolved particles do not necessarily re-dissolve back into the underlying perovskite upon oxidation. Instead, they may remain pinned to their initial locations, allowing one to subject them to further chemical transformations to alter their composition, structure and functionality dramatically, while preserving their initial spatial arrangement. We refer to this concept as chemistry at a point and illustrate it by tracking individual nanoparticles throughout various chemical transformations. We demonstrate its remarkable practical utility by preparing a nanostructured earth abundant metal catalyst which rivals platinum on a weight basis over hundreds of hours of operation. Our concept enables the design of compositionally diverse confined oxide particles with superior stability and catalytic reactivity. Metal nanoparticles prepared by exsolution at the surface of perovskite oxides are key species in catalysis and energy fields. Here, the authors develop a chemistry at a point concept by tracking individual nanoparticles with excellent activity and stability throughout various chemical transformations.